Risk Assessment and Regulation Strategy of Farmland Marginalization: A Case Study of Mengjin County, Henan Province - Guan, Xiaoke; Wang, Xiuli; Chen, Weiqiang (Frontiers in Environmental Science, 2022)
The marginalization of farmland is the progression of farmland utilization from high to low net profit, and the abandonment of farmland is its extreme form, and cultivated land marginalization is an important problem that needs to be properly controlled in the process of economic and social development. In this paper, cultivated land was extracted from the land database and evaluated from the aspects of natural suitability, farming convenience and farming opportunity cost, etc. By setting the combined weight of the three evaluation results and stacking them with the forest land extracted from remote sensing images, the potential risk range of cultivated land marginalization was identified, and an empirical study was carried out in Mengjin County, Henan Province. Results showed that: (1) the natural factors of cultivated land were stable and not easy to change, and the natural suitability was the basic condition that affected the marginalization of cultivated land. There was a spatial correlation between the natural suitability of cultivated land and the cultivation convenience, and the risk of marginalization of cultivated land with poor natural suitability and inconvenient cultivation conditions was higher. (2) The high-opportunity cost areas are mainly distributed in the inner suburbs of cities, and the cultivated land in this area is highly likely to be adjusted to high-benefit agriculture such as flowers, vegetables and sightseeing agriculture. Therefore, the risk of abandonment of cultivated land is less. (3) Adjusting cultivated land with poor natural suitability and inconvenient tillage conditions to forest land is conducive to the restoration of regional fragile ecology. Comprehensive improvement of cultivated land with high natural suitability but inconvenient tillage is an important way to delay the marginalization of cultivated land. This study provides a new idea for the formulation of farmland marginalization prevention and control policies at county level.